International Master’s Degree Students’ Experiences of Support at a Finnish University - Ballo, Anduena; Varis, Sotiria; Mathies, Charles; Filippou, Kalypso (Nordic Journal of Comparative and International Education (NJCIE), 2024)
This phenomenographic study explores international master’s degree students’ ways of experiencing support in Finnish higher education. The study draws on Schlossberg’s Transition Model and the Culturally Engaging Campus Environments Model as a conceptual framework. The phenomenographic analysis of 17 interviews with international master’s degree students identified four ways of experiencing support as: (a) study system adjustment, (b) learning enhancement, (c) personal growth, and (d) autonomy development. The findings identified participants’ experiencing support in relationships, use of information, communication, services, the flexibility of studies, learning and study environments. The presence of two indicators, Humanizing Educational Environments and Availability of Holistic Support suggested that the campus environment was culturally responsive to academic and personal support of international degree students. The findings contribute to the understanding of support for international degree students in higher education and may be used to develop services to support international degree students’ social, cultural, and career integration into host communities.